An Asymmetric Supercapacitor–Diode (CAPode) for Unidirectional Energy Storage. Issue 37 (5th August 2019) - Zhang, En; Fulik, Natalia; Hao, Guang‐Ping; Zhang, Han‐Yue; Kaneko, Katsumi; Borchardt, Lars; Brunner, Eike; Kaskel, Stefan
Abstract: A new asymmetric capacitor concept is proposed providing high energy storage capacity for only one charging direction. Size‐selective microporous carbons ( w <0.9 nm) with narrow pore size distribution are demonstrated to exclusively electrosorb small anions (BF4 − ) but size‐exclude larger cations (TBA + or TPA + ), while the counter electrode, an ordered mesoporous carbon ( w >2 nm), gives access to both ions. This architecture exclusively charges in one direction with high rectification ratios (RR=12), representing a novel capacitive analogue of semiconductor‐based diodes ("CAPode"). By precise pore size control of microporous carbons (0.6 nm, 0.8 nm and 1.0 nm) combined with an ordered mesoporous counter electrode (CMK‐3, 4.8 nm) electrolyte cation sieving and unidirectional charging is demonstrated by analyzing the device charge‐discharge response and monitoring individual electrodes of the device via in situ NMR spectroscopy. Abstract : Size matters : By coupling a carbon molecular sieve electrode with an ordered mesoporous carbon (CMK‐3), a new asymmetric capacitor concept with rectification function and high capacitance is realized. In situ NMR spectroscopy confirms the size exclusion and unidirectional charging mechanism.